2018
DOI: 10.1021/acsami.8b12897
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Gold Nanoparticle-Based Fluorescence Resonance Energy-Transfer Probe for Target Drug Delivery and Cell Fluorescence Imaging

Abstract: Drug delivery system has a profound significance for imaging capabilities and monitoring apoptosis process precisely in cancer therapeutic field. Herein, we designed cysteamine (CS)-stabilized gold nanoparticles, CS− gold nanoparticles (AuNPs)−doxorubicin (DOX), for fluorescence-enhanced cell imaging and target drug delivery. For cancer therapy, DOX was incorporated to CS−AuNPs by disulfide linkages which could be cleaved by glutathione (GSH) in cancer cells specifically. In addition, red-emissive DOX was quen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…As potential drug carriers, AuNPs have received considerable attention by many researchers [ 6 , 7 , 8 , 9 , 10 ], as it has been frequently reported that they can induce programmed cell death (i.e., apoptosis) [ 11 , 12 ]. Furthermore, as drug carriers, AuNPs can transport imaging and therapeutic agents, providing the possibility of diagnosis, treatment, and monitoring therapeutic progress, while AuNPs themselves do not participate in diagnosis or therapy [ 13 , 14 , 15 , 16 , 17 ]. However, AuNPs are rarely reported as agents that can inhibit cell proliferation and achieve both fluorescence-enhanced cell imaging and specific cell targeting.…”
Section: Introductionmentioning
confidence: 99%
“…As potential drug carriers, AuNPs have received considerable attention by many researchers [ 6 , 7 , 8 , 9 , 10 ], as it has been frequently reported that they can induce programmed cell death (i.e., apoptosis) [ 11 , 12 ]. Furthermore, as drug carriers, AuNPs can transport imaging and therapeutic agents, providing the possibility of diagnosis, treatment, and monitoring therapeutic progress, while AuNPs themselves do not participate in diagnosis or therapy [ 13 , 14 , 15 , 16 , 17 ]. However, AuNPs are rarely reported as agents that can inhibit cell proliferation and achieve both fluorescence-enhanced cell imaging and specific cell targeting.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles have been demonstrated to be a promising drug delivery scaffold because they are known to be biocompatible, [ 23,24 ] simple to synthesize, and can have functional surface moieties. [ 25–33 ] We have developed a functional gold nanoparticle that enables the selective, stepwise release of two distinct payloads by altering the wavelength of illumination ( Figure ). With this nanoparticle, we were able to achieve stepwise, wavelength selective, payload release from single nanoparticles in live cells, which has not been achieved with previously reported systems.…”
Section: Figurementioning
confidence: 99%
“…To achieve targeted drug delivery for tumor diagnosis and treatment, reduce toxic and side effects on normal cells, and assist in fluorescence imaging to detect the GSH content, Ding et al . designed and prepared cysteine (CS)‐stabilized gold nanoparticles (CS‐AuNPs‐DOX fluorescent nanoprobe) [59] . The change of fluorescence signal of the drug loaded with the fluorescent probe was used to indicate the content of RTCs, so as to image the lesion, help diagnose the disease, and complete the targeted delivery of the drug.…”
Section: Biological Applications Related To Rtcsmentioning
confidence: 99%